The Effect of Video Media Health Education on Marriage Age Maturity Knowledge (PUP) in Adolescents - Sundayana, Dewi P. F; Suranata, Faradilla Miftah; Rimporok, Merry H. (Journal of Midwifery and Nursing, 2025)
Marriage Age Maturity is a program of National Family Planning Coordinating Agency (BKKBN), this program is expected to help adolescents protect themselves against marriage at the age of less than 19 years. The number of cases of underage marriage is due to the lack of knowledge possessed by students, there are several steps to increase students' knowledge, one of them by providing health education. The purpose of this study was to determine the effectiveness of health education video on marriage age maturity (PUP) knowledge in adolescents at SMP Negeri 4 Sanana Utara. This study used a quasi experiment with one group pre test - post test research design. Taken 30 respondents by total sampling technique. The data collection using a questionnaire sheet. Furthermore, the data that has been collected be analyzed using the Mc-Nemar statistical test with a significant level of pre-post knowledge with p-value (? 0.05). The results of the Mc-Nemar test analysis for the level of knowledge obtained a p value of 0.000 (<?= 0.05), the results of this study indicate that Ha is accepted. The conclusion in this study, health education video are effective on marriage age maturity (PUP) knowledge in adolescents at SMP Negeri 4 Sanana Utara. The results of this study are expected to be input and development material, especially in marriage age maturity knowledge. Researchers suggest, the schools play a role in increasing students' knowledge about marriage age maturity by coordinating with BKKBN to create a Youth Information and Counseling Center (PIK-R) at school.font).